1983
DOI: 10.2172/6180868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hanford High-Level Waste Components on Sorption of Cobalt, Strontium, Neptunium, Plutonium, and Americium on Hanford Sediments

Abstract: RHO-REST -1 P WER Effects of H anford High-Level ft W aste Com ponents on Sorption o f Cobalt, S tro ntium , N eptunium , Plutonium , and A m ericium on H anford Sedim ents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 0 publications
2
58
0
Order By: Relevance
“…Most ligands are also chemically unstable and are continually being transformed into molecules with even weaker complex- ' forming capabilities. Delegard and Gallagher (1983) show in an empirical fashion that relatively high concentrations of chelating agents [HEDTA to 0.1 My EDTA to 0.05 My hydroxyacetate to 0.1 M, and citrate to 0.03 MI did not increase the solubility of plutonium in tank environments. Toste et al (1984Toste et al ( ,1987) discuss procedures to analyze for specific chelatinglcomplexing agents in complex waste streams.…”
Section: 25mentioning
confidence: 86%
See 1 more Smart Citation
“…Most ligands are also chemically unstable and are continually being transformed into molecules with even weaker complex- ' forming capabilities. Delegard and Gallagher (1983) show in an empirical fashion that relatively high concentrations of chelating agents [HEDTA to 0.1 My EDTA to 0.05 My hydroxyacetate to 0.1 M, and citrate to 0.03 MI did not increase the solubility of plutonium in tank environments. Toste et al (1984Toste et al ( ,1987) discuss procedures to analyze for specific chelatinglcomplexing agents in complex waste streams.…”
Section: 25mentioning
confidence: 86%
“…(1993), Hobbs andEdwards (1993), Hobbs (1995), Delegard et a1. (1984), Delegard and Gallagher (1983), and Delegard (1 995). However, in a recent study involving waste supernatants, Hobbs and KarrakeP) identified PuO,*XH,O in the.…”
Section: Precipitation Of Plutonium Hydroxide Phasementioning
confidence: 99%
“…[3,4] To address these issues, a filtration study was performed using the sixth set of samples equilibrated at 25 C to determine if submicron, actinide-containing particles in the filtered solutions contributed to the data scatter and the elevated Am solubilities. The sample preparation was performed by removing a 4-5 mL aliquot of salt solution from a sample bottle using a disposable syringe and expelling through a 0.45 μm disk filter into a clean glass vial.…”
Section: Filtration Studymentioning
confidence: 99%
“…[2] The practical usefulness of the model is limited since other constituents in the waste solution can change the Pu solubility by as much as three orders of magnitude for a given hydroxide concentration. Americium solubility in SRS waste solutions has never been systematically studied; however, there is limited data available for Hanford tank waste [3] and in pure sodium hydroxide solutions. [4] The objective of this work was to measure the solubility of Pu and Am in simulated SRS waste solutions over a broader range of solution compositions and temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation